2021
DOI: 10.1021/acs.jmedchem.1c00010
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biphenyl Pyridines as Potent Small-Molecule Inhibitors Targeting the Programmed Cell Death-1/Programmed Cell Death-Ligand 1 Interaction

Abstract: With the successful clinical application of anti-programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) monoclonal antibodies (mAb), targeting the PD-1/PD-L1 interaction has become a promising method for the discovery of cancer therapy. Due to the inherent limitations of antibodies, it is necessary to search for small-molecule inhibitors against the PD-1/PD-L1 axis. We report the design, synthesis, and evaluation in vitro and in vivo of a series of novel biphenyl pyridines as the inhibitors of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 27 publications
(98 reference statements)
2
34
0
Order By: Relevance
“…As shown in Table , by incorporating the difluoromethyleneoxy motif as an unusual bioisosteric replacement of the methoxy linkage and retaining other structural components intact, compound 25 displayed an IC 50 of 31.87 nM against the PD-1/PD-L1 interaction, which is slightly more potent than reference compound 2 (IC 50 = 48.2 nM). A quick screening of a small set of alkylamino alcohols/acids widely used in the literature ,, as the solvent interaction structural motif indicated that all the resulting compounds 26–28 retained high inhibitory activity against the PD-1/PD-L1 interaction, and compound 28 bearing a 2-amino-2-methylpropane-1,3-diol component showed more increased potency with an IC 50 value of 16.31 nM. Keeping the 2-amino-2-methylpropane-1,3-diol component intact and changing the substitution pattern of the central tetra-substituted phenyl ring from 3-methyl to the 4-chloro pattern led to compound 29 , showing a much improved potency with an IC 50 value of 5.93 nM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table , by incorporating the difluoromethyleneoxy motif as an unusual bioisosteric replacement of the methoxy linkage and retaining other structural components intact, compound 25 displayed an IC 50 of 31.87 nM against the PD-1/PD-L1 interaction, which is slightly more potent than reference compound 2 (IC 50 = 48.2 nM). A quick screening of a small set of alkylamino alcohols/acids widely used in the literature ,, as the solvent interaction structural motif indicated that all the resulting compounds 26–28 retained high inhibitory activity against the PD-1/PD-L1 interaction, and compound 28 bearing a 2-amino-2-methylpropane-1,3-diol component showed more increased potency with an IC 50 value of 16.31 nM. Keeping the 2-amino-2-methylpropane-1,3-diol component intact and changing the substitution pattern of the central tetra-substituted phenyl ring from 3-methyl to the 4-chloro pattern led to compound 29 , showing a much improved potency with an IC 50 value of 5.93 nM.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, optimization of the methoxy (−CH 2 O−) linker was conducted by two groups. Jiang’s group removed the linker, and Li’s group replaced methoxy with the methylamino (−CH 2 NH 2 −) group, yielding compounds 7 and 8 with IC 50 values of 3.8 and 12.0 nM, respectively. Meanwhile, compounds 9 and 10 with high PD-1/PD-Ll blocking activity (IC 50 : 12.5 and 9.1 nM, respectively) were reported by the Chen group through modifying the solvent–interaction region. , More recently, Zhu and co-workers disclosed compound 11 bearing a taurine moiety located in the solvent interaction region with an IC 50 value of 9.1 nM.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by recent findings concerning the effect of pomalidomide on PD-L1 induction [ 25 ] and postulated activity of PD-L1-targeting PROTACs [ 26 , 27 ], we designed several PD-L1–linker–pomalidomide synthetic constructs based on our recently published PROTAC and PD-L1 work [ 24 , 28 ]. The syntheses of the proposed inhibitors are shown in Scheme 1 , Scheme 2 and Scheme 3 and comprise the known syntheses of the PD-L1 inhibitors BMS-1166 and BMS-202 [ 17 , 19 , 29 , 30 ], terphenyl [ 31 , 32 ] and imidazopyridines [ 24 ], which then were linked together with pomalidomide derivatives to form the desired chimeras. All the pomalidomide intermediates used in the synthesis were obtained according to the known protocols.…”
Section: Resultsmentioning
confidence: 99%
“…A number of reports are also emerging recently from the industry and academia using the privileged structure of biphenyl-containing compounds and their various derivatives to improvise the druggability of the molecules. This includes scaffold based on nicotinyl alcohol ether derivative ( 45 – 47 ), resorcinol dibenzyl ether ( 48 ), 4-phenylindoline derivatives ( 49 ), combining two privileged scaffolds such as biphenyl backbone structure and 2-amino-pyrimidine structure ( 50 ), biphenyl-4-carboxamide derivatives ( 51 ), incorporating taurine moieties ( 52 ), 1-methyl-1H-pyrazolo[4,3-b] pyridine derivatives ( 53 ), replacing the linker connecting aryl group and biaryl core with a novel amine linker ( 54 ), a series of novel biphenyl pyridines derivatives lacking linker ( 55 ), biphenyl methyl nitrophenyl core unit ( 56 ), and terphenyl scaffold derived from the rigidified biphenyl inspired structure ( 57 ). Representative structures of the compounds disclosed are presented in Figure 3 .…”
Section: Two Major Classes Of Small Molecules Targeting Pd1-pd-l1 Axismentioning
confidence: 99%